2020
DOI: 10.1007/s00415-020-10019-x
|View full text |Cite
|
Sign up to set email alerts
|

Telling friend from foe in emergency vertigo and dizziness: does season and daytime of presentation help in the differential diagnosis?

Abstract: Distinguishing between serious (e.g., stroke) and benign (e.g., benign paroxysmal positional vertigo, BPPV) disorders remains challenging in emergency consultations for vertigo and dizziness (VD). A number of clues from patient history and clinical examination, including several diagnostic index tests have been reported recently. The objective of the present study was to analyze frequency and distribution patterns of specific vestibular and non-vestibular diagnoses in an interdisciplinary university emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
1
2
1
Order By: Relevance
“…[6,8,13] In addition, 1 recent study reported that incidence of acute unilateral vestibulopathy due to viral etiology, which included VN, peaked in autumn, not in spring and early summer, among patients in the emergency department. [15] In general, there was no significant monthly and seasonal variations in number of visits for VN in the present study. Although there was an increasing trend in incidence of VN in summer, it was not In addition, in our analyses of subgroups according to sex and age, there were no significant monthly and seasonal variations in number of visits for VN.…”
Section: Discussioncontrasting
confidence: 48%
“…[6,8,13] In addition, 1 recent study reported that incidence of acute unilateral vestibulopathy due to viral etiology, which included VN, peaked in autumn, not in spring and early summer, among patients in the emergency department. [15] In general, there was no significant monthly and seasonal variations in number of visits for VN in the present study. Although there was an increasing trend in incidence of VN in summer, it was not In addition, in our analyses of subgroups according to sex and age, there were no significant monthly and seasonal variations in number of visits for VN.…”
Section: Discussioncontrasting
confidence: 48%
“…Our study shows HC-BPPV recurrence is not correlated with age, gender, seasons, and blood pressure status, which is consistent with some previous studies ( 21 – 23 ), while other studies presented conflicting results, including our previous study on PC-BPPV ( 16 ). The results also showed that the recurrence of BPPV was closely associated with the female gender.…”
Section: Discussionsupporting
confidence: 91%
“…However, distinguishing between serious and benign disorders caused by VD remains challenging in emergency consultations, even for experienced doctors. Additionally, misdiagnosis may be fatal for patients, e.g., serious disorders caused by a posterior stroke [ 4 ]. Therefore, the challenges of making a fast and correct diagnosis remind us of the importance of the clinical teaching of VD-related diseases.…”
Section: Introductionmentioning
confidence: 99%